KOMUNIKASI INSTRUKSIONAL GURU DALAM PROSES PEMBELAJARAN PROGRAM KEAHLIAN REKAYASA PERANGKAT LUNAK DI SMKN2 PEKANBARU - Anggraini, Mutia; Salam, Noor Efni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Software Engineering is one of the majors on SMKN2 that many of its enthusiasts. In this department studied is not just about computers but students are taught to create a program that will be used on computer software. The creation of an application program is guided by the teacher who instructs the students. In giving instruction teachers use instructional communication in the learning process. This study aims to determine the method of instructional communication, instructional communication media, and communication barriers that occur in the learning process of software engineering skills program.This research uses qualitative research method with symbolic interaction approach. Informants from this research are three teachers, three students and headmaster SMKN 2 Pekanbaru, while the object of this research is teacher instructional communication in learning process of software engineering skill program at SMKN 2 Pekanbaru. Data collection techniques used in the form of observation, interview and documentation. In achieving the validity of the data in this study, the authors use extension of participation and triangulation.The results showed that instructional communication of teacher in learning process of software engineering skill program at SMKN 2 Pekanbaru using three instructional communication method that is lecture method, individual method and method of discussion and presentation. The methods used are very helpful in understanding the students making the application program. The media used are audio media, visual media, audiovisual media and media aids. Media is often used and effective in its use of audio media and media aids. In the process of learning software engineering skills program is inseparable from the barriers that can affect the smooth learning. Instructional communication barriers that occur are the barriers to the source, obstacles to the channel, barriers to communicants and psychological barriers. Teachers as communicators use verbal and nonverbal symbols in instructional communication activities.Keyword : instructional communicatio, learning, learning process